Exploring the Rāmāyana relief as a pillar supporting cultural tourism identity at the Bali international convention center - I Gusti Ngurah Wija Negara; Subhajit Choudhury; Sugiarti (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: This study explores the presence of 20 Rāmāyana relief panels at the Bali International Convention Centre (BICC) in Nusa Dua, serving as pillars of Balinese cultural tourism identity. The reliefs represent the Kakawin Rāmāyana narrative, which has been adapted into Balinese carving aesthetics through the technique of multiple-layer carving, integrating local flora and fauna symbols, Balinese Hindu cosmological principles, and the spiritual values of dharma, satya, and bhakti. Methods: Using a descriptive qualitative method with an interpretive approach, this research involved field observations, in-depth interviews with managers, and visual analysis. Findings: The results show that the relief serves as an aesthetic representation that constructs the spiritual and visual image of a world-class cultural destination; as an educational medium that facilitates the transfer of moral values, cross-cultural learning, and visual cultural diplomacy; and as a reinforcement of the socio-economic dimension through the empowerment of local artists, the preservation of traditional carving techniques, and the increase in the economic value of creativity in the premium tourism industry. Conclusion: This study confirms that the Rāmāyana relief is a strategic instrument for preserving Balinese cultural identity amid globalization, but it remains limited to a single location. Novelty/Originality of this article: Therefore, further research with a comparative, quantitative approach is recommended to broaden the generalizability of the findings.